2009
DOI: 10.1093/humrep/dep196
|View full text |Cite
|
Sign up to set email alerts
|

Malignant cells are not found in ovarian cortex from breast cancer patients undergoing ovarian cortex cryopreservation 

Abstract: Using the methodology of the SLN our data suggest the absence of tumour cells in biopsies obtained from patients undergoing ovarian cortex cryopreservation to preserve their fertility potential, although future methods of cancer screening may change our perception of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 32 publications
1
58
0
4
Order By: Relevance
“…Azem et al most recently found no evidence of neoplastic involvement in 40 ovarian biopsy specimens of various cancer patients intending to undergo ovarian tissue cryopreservation 62 . Similar results have previously been obtained, particularly in cases of breast cancer and lymphoma [63][64][65] . However, in 2010, Rosendahl and colleagues used polymerase chain reaction to examine the extracted ovarian tissue of 26 patients with leukemia and found that 75% of cells showed leukemic infiltration, contrary to the 0% rate of abnormality noted on histologic examination 66 .…”
Section: Ovarian Tissue Cryopreservation and Transplantationsupporting
confidence: 90%
“…Azem et al most recently found no evidence of neoplastic involvement in 40 ovarian biopsy specimens of various cancer patients intending to undergo ovarian tissue cryopreservation 62 . Similar results have previously been obtained, particularly in cases of breast cancer and lymphoma [63][64][65] . However, in 2010, Rosendahl and colleagues used polymerase chain reaction to examine the extracted ovarian tissue of 26 patients with leukemia and found that 75% of cells showed leukemic infiltration, contrary to the 0% rate of abnormality noted on histologic examination 66 .…”
Section: Ovarian Tissue Cryopreservation and Transplantationsupporting
confidence: 90%
“…In women with breast cancer, neither Sánchez-Serrano et al [38] nor Rosendahl et al [36] detected the presence of ovarian metastases in cryopreserved ovarian tissue by morphological or immunohistochemical studies. Sanchez-Serrano et al [38] analyzed 100 frozen-thawed ovarian cortical biopsies from 63 patients and 6 entire pieces of frozen-thawed cortex from patients diagnosed with IDC by histology or immunohistochemistry using cytokeratin CAM 5.2, gross cystic disease fluid protein-15 (GCDFP15), Wilms' tumor antigen-1 (WT1) and mammaglobin 1 as markers. Rosendahl et al [36] examined cryopreserved ovarian cortical biopsies from 51 patients with breast cancer by histology and immunohistochemistry with another set of markers (cytokeratin 7, CK-AECAM, WT1 and cancer antigen 125).…”
Section: Introductionmentioning
confidence: 95%
“…Breast cancer is our second most frequent indication for OTC and, so far, no malignant cells have been found in ovarian tissue from breast cancer patients by immunohistochemistry [47,52]. Nevertheless, more sensitive approaches need to be developed to further ascertain the safety of ovarian tissue grafting in breast cancer patients.…”
Section: Risk Of Malignant Cells In Cryopreserved Ovarian Tissuementioning
confidence: 99%